PEMBINAAN KARAKTER KEWIRAUSAHAAN PESERTA DIDIK MELALUI PROGRAM MARKET DAY DI SD NEGERI 131/IV KOTA JAMBI - Ismaya, Mayang; Sofwan, Muhammad; Budiono, Hendra (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to describe the process of fostering entrepreneurial character in students through the market day program at SD Negeri 131/IV Jambi. The research was conducted using a qualitative case study method by carrying out interviews and direct observations with students. The results show that students learn to create, produce, and sell products, which fosters creativity, innovation, self-confidence, leadership, as well as collaboration and responsibility. The market day program also helps students develop key entrepreneurial traits such as creativity, self-confidence, adaptability, decision-making, financial responsibility, effective communication, and teamwork. It can be concluded that this program builds future-oriented character and motivates students to become entrepreneurs.